Characteristics of autologous protein solution and leucocyte-poor platelet-rich plasma for the treatment of osteoarthritis of the knee - Wasai, Shiho; Sato, Masato; Maehara, Miki; Toyoda, Eriko; Uchiyama, Ryoka; Takahashi, Takumi; Okada, Eri; Iwasaki, Yoshiko; Suzuki, Satoko; Watanabe, Masahiko (Scientific reports, 2020)
Recently, platelet-rich plasma (PRP) has received attention as a treatment for patients with osteoarthritis of the knee (OAK), a chronic degenerative disease, to bridge the gap between conservative and surgical treatments. Here, we investigated the differences in the humoral factors present in two types of PRP purified using the Autologous Protein Solution (APS) kit (group Z; leucocyte-rich PRP) or the Cellaid Serum Collection Set P type (group J; leucocyte-poor [LP]-PRP). Differences in humoral factors between healthy subjects (n = 10) and OAK patients (n = 12; group Z = 6, group J = 6), and the relationship between humoral factors and clinical outcome scores were investigated. Both anti-inflammatory and inflammatory cytokines were highly enriched in APS. The concentrations of tumour necrosis factor (TNF)-α, platelet-derived growth factor, fibroblast growth factor, soluble TNF-receptor 2, soluble Fas and transforming growth factor-β1 were higher in group Z, while the total amounts were higher in group J. The concentration of interleukin-1 receptor antagonist was positively correlated with the magnitude of change in the clinical outcome score and may contribute to improving knee-joint function. This is the first description of the humoral factors in APS and LP-PRP prepared from healthy subjects or OAK patients of Asian descent.